2022
DOI: 10.3390/jintelligence10030071
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Teaching Styles on the Learning Academic Confidence of Teachers in Training

Abstract: The objective of this research was to analyze the mediation of academic engagement and the satisfaction of basic needs between teaching styles and academic confidence amongst teachers during initial training. The research design was observational, descriptive, cross-sectional, and non-randomized. In total, 920 university students in initial teacher training participated (61.85% women) (Mage = 24.73; SD = 5.34). The scales of interpersonal teaching styles, the satisfaction of basic psychological needs, academic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 72 publications
0
9
0
1
Order By: Relevance
“…Recent advances in the educational field have tried to examine how socio-contextual classroom environments (i.e., the social-psychological environment) affect motivational processes, as well as the role the teacher trainer might adopt in the initial teacher training context [11][12][13][14]. In this sense, following self-determination theory (SDT) [15], various interpersonal teaching styles are recognised (e.g., autonomy support and controlling style) in the teaching intervention.…”
Section: Of 14mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent advances in the educational field have tried to examine how socio-contextual classroom environments (i.e., the social-psychological environment) affect motivational processes, as well as the role the teacher trainer might adopt in the initial teacher training context [11][12][13][14]. In this sense, following self-determination theory (SDT) [15], various interpersonal teaching styles are recognised (e.g., autonomy support and controlling style) in the teaching intervention.…”
Section: Of 14mentioning
confidence: 99%
“…Previous research [33] has operationalized academic engagement across different dimensions: vigour, dedication, and absorption. Specifically, research in the teacher training context has shown the importance of academic engagement both as a consequence of socio-contextual classroom environments [14] and as a mediator between educational outcomes [13]. Although the use of academic engagement as an antecedent of future behaviours has been evidenced [34], few studies have evaluated its possible positive influence on behavioural intention (i.e., the intention to be a teacher) [35] despite its relevance in the teacher training context [8,10,36].…”
Section: Academic Engagementmentioning
confidence: 99%
“…Research on 637 Spanish students reported a direct relationship between academic engagement and study satisfaction (Froment et al, 2023). Additionally, academic engagement is directly linked to the quality of university education (Granero-Gallegos et al, 2022) and positively associated with study satisfaction (Hensley et al, 2021;Arredondo-Salas et al, 2022). Furthermore, research confirms that dimensions of academic engagement enhance academic performance and satisfaction with studies (López-Aguilar et al, 2021).…”
Section: Mamanimentioning
confidence: 88%
“…Teaching style is another relevant factor. Styles that promote autonomy are positively related to students' academic confidence, while more controlling styles have a negative impact (Granero-Gallegos et al, 2022). Additionally, academic engagement, which involves active participation and interest in learning, is fundamental for student satisfaction (Hensley et al, 2021;Arredondo-Salas et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Ganero-Gallegos et.al. (2022) [3] analyzed the meditation of academic engagement and the satisfaction of basic needs between teaching styles and academic confidence amongst teachers during initial training. A sample of 920 university students in initial training participated.…”
Section: Research Effort In This Areasmentioning
confidence: 99%